General Equilibrium Effects of Targeted Transfers: The case of the Earned Income Tax Credit (EITC) - Charles Gottlieb; Maren Froemel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Transfers have recently become the most important fiscal policy tool of the U.S. Government. Moreover, within the transfer category, refundable tax credits have reached the same magnitude as unemployment insurance, yet little research documents the macroeconomic implications of tax credits. The existing literature on the effect of tax credits, abstract from behavioral responses to policy changes and are silent on potential general equilibrium effects. This paper fills this gap by addressing these two shortcomings of the existing literature, by modeling the Earned Income Tax Credits (EITC) in an infinite horizon economy with exogenously incomplete asset markets and heterogeneous agents. In particular, we assess the welfare effects of the EITC and analyze how effective targeted transfers are in alleviating distortions arising from incomplete financial markets, and contribute to the debate on labor supply responses to EITC. We also conduct two policy exercises. First, we evaluate the impact of a more generous targeted transfer program on welfare and aggregate outcomes, and thereby uncover the distributional properties of this fiscal policy tool. Secondly, we assess whether targeted transfers are a better policy tool than lump sum transfers and show that targeted transfers are indeed welfare enhancing as they achieve more redistribution at lower tax rates, but that they lead to a less efficient production at the aggregate level.
Keywords: B22; H23; H31; 330